Answer:
Step-by-step explanation:
Given the expression:
![(1)/(2x)+3=(2)/(3x)+1](https://img.qammunity.org/2023/formulas/mathematics/college/9xe85obfspuyixf8r2oumvstk6fqg7hfee.png)
To solve this, first collect the like terms as:
![\begin{gathered} (1)/(2x)-(2)/(3x)=1-3 \\ \\ (1)/(2x)-(1)/(3x)=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pqn3h2dmj93qyhgerthxf0xbmz56y60r9u.png)
Next, we can multiply both sides of the equation by 6x to nullify the fractions on the left-hand side
![\begin{gathered} (6x)/(2x)-(6x)/(3x)=-2*12x \\ \\ 3-2=-24x \\ \\ 1=-24x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nqorrma9uo1pown7kharp27ljh6nh1kdo0.png)
Finally, divide both sides by the coefficient of x, which is -24
![\begin{gathered} x=(1)/(-24) \\ \\ x=-(1)/(24) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7x8h2qurpcybjx9989thh7bzeo572zeywi.png)